The role of task complexity and task motivation in language production - Umi Kalsom Masrom,; Nik Aloesnita Nik Mohd Alwi,; Nor Shidrah Mat Daud, (Penerbit UKM, 2015)
This study investigates the relationship between the cognitive demands of task complexity and learners‘ motivation towards several tasks using task-based instruction during asynchronous computer-mediated communication (CMC) writing tasks. According to Robinson‘s Cognition Hypotheses (2001a, 2005, 2007), the production of language would be different when certain manipulation of task complexity was made. The tasks were manipulated following two variables from the Cognition Hypotheses, along resource-directing (+/- causal reasoning demand) and resource-dispersing (+/- task structure) dimensions. Eighty-eight undergraduate students from one of the technical universities in Malaysia were divided into four groups and assigned with a writing task. After the participants have completed the writing tasks, they were interviewed and asked to complete a questionnaire to gauge their motivation towards the tasks. Participants‘ written language production was coded and analyzed using syntactic and lexical complexity measures. Further analysis of the data was conducted using Multivariate Analysis of Variance (MANOVA) and correlational analysis. Analyses of the results showed that there is a correlation between task complexity and task motivation among learners. However, the correlation is only evident in lexical complexity production and no correlation was found for any of the syntactic complexity measures. This study is significant as it explores the roles of task complexity and task motivation in mediating the production of language. It also highlights how the manipulation of task complexity would encourage the production of the language in terms of its complexity.